Giordano Bruno and the Hermetic tradition - Yates, Frances Amelia (Routledge classics., 2002)
In 1600 the renegade philosopher and theologian Giordano Bruno was burnt at the stake in Rome. One of the most notorious figures of his times, his crime was to preach a doctrine of brotherhood, peace and free love. Four centuries later Bruno is known as the Prophet of the New Age and his vision of an infinite universe grounded in science is increasingly celebrated. One of the main forces behind his rediscovery was the great British historian Frances Yates. It was she who pioneered the study of the hugely influential occult and hidden traditions that had previously been ignored in the histories of European thought. In calling attention to Giordono Bruno, Yates paved the way for a revaluation of the esoteric influences at play during the onset of the modern era. Today, when traditional answers about the universe and our place within it are under increasing scrutiny, Giordono Bruno and the Hermetic Tradition proves itself a true classic for our time.